Aspectos geohidrológicos y sedimentológicos de los flujos de lodo asociados al terremoto de Cinchona (Mw 6,2) del 8 de enero del 2009, Costa Rica - Alvarado, Guillermo E. (Universidad de Costa Rica, 2009)
The Cinchona earthquake (Mw 6.2) located 6.5 km east of the active crater of Poás, triggered several landslides (rock fall, rotational and translational slides), which in combination with existing pore water within the landslide mass in intense tropical weathering volcanic soils, local aquifers deformation, and mixing of fluvial waters into the moving sediment mass, produced high destructive debris flows along the Seco, María Aguilar, Cariblanco, Ángel, La Paz, Sarapiquí, Mataste and Tigre rivers. The deposits totaling 0.5-3 m in thickness, consisting of angular to rounded volcanic clasts, matrix-supported, very poorly sorted gravels, interpreted as a non-eruptive lahar or debris flow diamicton (volcanic muddy gravelly sands) deposits, specifically as a cohesive (5-7% clay) woody mud flows. Logs and other organic debris are often incorporated in the levees and the preserved front flows were well defined and 1.5 m high, suggesting a relative moderate viscosity flow. Megablocks of ignimbrite (60-200 m3) from the bedrock were incorporated and broken up into individual fragments. The proximal and medial cannon-side facies are represented by thin (0.1-1 m) veneers deposits on steep slopes with abundant evidences of marks peak-flow levels (mudline, striations) and bulking (incorporation of boulders, anthropogenic and log debris). In open spaces of the piedmont and alluvial plain, instead, the flow was of hypenconcentrate type due mixing with the stream water downstream, and present a bouldery flow channel deposit surface gradating to smooth flow deposit surface, and abundance evidence of cataclasis (breakage of clast owing to collisions). The velocity of the flows were estimated for several rivers variable between 13.3 and 4.8 m/s (48-17.5 km/h), with super-elevations in the channel rivers up to 35 m as a steep-fronted head of at least 5-15 m, but after the piedmont, it was only 1-0.5 m high and it move at relative slower velocities of 2.5-10 m/s (9-36 km/h). The flow pushes some stream water along the channel in front of it, a phenomenon termed miscible displacement. The total volume of sediments is crudely estimated in at least 2.5-3.5 x 106 m3. The apparent coefficient of friction or fahrböschung number was for the debris and hypoconcentrated flows of 0.09 and 0.06, respectively. Six bridges, several pasture land, the electromechanical equipment at the Cariblanco powerhouse were destroyed. The caudal was estimated in the Sarapiquí river at Cariblanco power house in 4374-5994 m3/s. The strong motion equipment registered peak accelerations of 25.64 cm/s2 due the debris flow, and the spectrum of seismic record produced is characterized by frequencies between 7 and 37 Hz. The protection dike at the Cariblanco power house produce a change in the hydrologic and reologic condition of the flow, from a supercritic flow with antidunes to a subcritic flow (Froude number: 0.48-0.84) with lower velocity of 1.6-3.2 m/s (6.1-11.7 km/h), favoring the loss its bedload zone transported as traction carpet, and therefore with a less destructive effects on the buildings due a relatively diluted overlying flow zone (tranquil flow) carrying suspended sediment and tree debris. The mudflows produced strong vertical and lateral erosion, killed all the fluvial fauna, resulted in profound changes in the hydrologic stability for years of the Sarapiquí drainage basin.